(untitled) (المجلة الدولية للبحوث العلمية, 2025)
Architecture is the science of origins by which the elements of composition change their status and composition (relationship) and its subject is the elements of composition. Architecture is complex forms some (related to the feeling / moral aspects). [1] Therefore, the research problem was concerned with the nature of the perception of the architectural event and its spread among peoples within the following possibilities: 1- Is the image of the architectural event through time, conflict and dialogue at other times? 2- Or is it that the image of the architectural event is through dialogue as a thought and the use of dialogue as a mechanism? 3- Is the image of the architectural event formed through the conflict as an instinct and the use of dialogue as a mechanism to achieve it? 4- Or is the conflict a degree of dialogue and that dialogic architecture is not a part of the equation but is the product of the images resulting from moving architecture through degrees of dialogue? Through the events and struggles that the architectural scene witnessed in the spread of architecture among peoples, it confirms that it passed through the three points. The research tries to put its hypothesis based on the eternal relationship between conflict and dialogue since the inception of creation, which applies to architecture, so the research assumes that to obtain an architecture that is spiritual and enjoys privacy. The place can live for the longest possible period. There must be a relationship transferring the image from conflict as an intellectual reality to dialogue as a practical reality that architecture pursues to reach its goals. This is done by tracing the process of transferring the image of the architectural thought between power and action, considering that the conflict is a degree of dialogue to understand the problematic of perceiving the architectural event to reach the goals of dialogic architecture.